Hedgehog targets in the Drosophila embryo and the mechanisms that generate tissue-specific outputs of Hedgehog signaling. - Biehs, B.; Kechris, K.; Liu, S.; Kornberg, T.B. (Development, 2010)
Paracrine Hedgehog (Hh) signaling regulates growth and patterning in many Drosophila organs. We mapped chromatin binding sites for Cubitus interruptus (Ci), the transcription factor that mediates outputs of Hh signal transduction, and we analyzed transcription profiles of control and mutant embryos to identify genes that are regulated by Hh. Putative targets that we identified included several Hh pathway components, mostly previously identified targets, and many targets that are novel. Every Hh target we analyzed that is not a pathway component appeared to be regulated by Hh in a tissue-specific manner; analysis of expression patterns of pathway components and target genes provided evidence of autocrine Hh signaling in the optic primordium of the embryo. We present evidence that tissue specificity of Hh targets depends on transcription factors that are Hh-independent, suggesting that `pre-patterns' of transcription factors partner with Ci to make Hh-dependent gene expression position specific.